Silagem de grão de milho reidratado com soro de leite e água - Andrade, Luiz Paulo de (2013)
Given the intensification of animal production , the use of technology Wet grain silage can contribute significantly to improving productivity indices , highlighting the economic importance of this as a constituent of food rations . The objective of this research was to investigate the nutritional value of silage maize grain rehydrated at different moisture contents . The experiment was conducted at the Faculty of Agronomy of the University José do Rosário Vellano , Campus Alfenas - MG . The experimental design was completely randomized with a 3x2x2 , and ( rehydration grain at three moisture contents ; rehydrated in saline and water with and without inoculant ) totaling 12 treatments and 4 replications ; Results concerning the characteristics bromatological underwent to analysis of variance ( ANOVA ) using the statistical program SISVAR ( FERREIRA , 2003) . It was found lower pH in silage inoculated when there rehydration with acid whey . Inoculation biological silage moisture corn resulted in higher concentration of lactic acid . Inoculation of silage resulted in higher concentrations of acetic and propionic acid . The propionic acid concentration remained similar between treatments evaluated in this study , although the concentration was low in all of them . Rehydrated silages with whey had higher dry matter silages compared with rehydrated with water . The concentration of protein (CP ) in silage moisture corn was only changed due to the liquid used in rehydration . The NDF was reduced by rehydration with acid whey , whether or not the application of the inoculant . The concentration of ADF increased linearly in the control treatment due to rehydration using acid whey , while the inoculated silage , there was greater concentration rehydration by 40%.